RETHINKING SUSTAINABLE DEVELOPMENT economic integration and public policy. - Tan, Seck (ROUTLEDGE, 2024)
This book demonstrates falsified economic performance of global economies when the environment is not recognised as a capital, and when the ecosystem is overlooked towards sustainable development. Seck begins with an analysis of standard macroeconomic framework and policy practice. He argues, with reference to environmental accounting literature, that environmental capital must form an integral component of economic measurement. This paves the way for an alternative environmental-macroeconomics framework for policy analysis that promotes sustainable development. The book demonstrates how environmental capital can be measured with reference to select OECD countries and provides a methodology for analysing how macroeconomic goals are related to a steady-state economy. Seck then concludes with a summary of the conflict between current economic growth and ecosystem preservation, and outlines possible policy improvements and directions for research. Rethinking Sustainable Development is an invaluable reference for policymakers as well as researchers and students of environmental economics, sustainable development, and macroeconomics.